Pediatric Sensorineural Hearing Loss, Part 1: Practical Aspects for Neuroradiologists - Huang, B.Y.; Zdanski, C.; Castillo, M. (American Journal of Neuroradiology, 2012)
SUMMARY: SNHL is a major cause of childhood disability worldwide, affecting 6 in 1000 children. For children with prelingual hearing loss, early diagnosis and treatment is critical to optimizing speech and language development, academic achievement, and social and emotional development. Cross-sectional imaging has come to play an important role in the evaluation of children with SNHL because otolaryngologists routinely order either CT or MR imaging to assess the anatomy of the inner ears, to identify causes of hearing loss, and to provide prognostic information related to potential treatments. In this article, which is the first in a 2-part series, we describe the basic clinical approach to imaging of children with SNHL, including the utility of CT and MR imaging of the temporal bones; we review the most recent proposed classification of inner ear malformations; and we discuss nonsyndromic congenital causes of childhood SNHL. ABRauditory brain stem responseBCNCbony cochlear nerve canalCISSconstructive interference in steady stateCMVcytomegalovirusCNcochlear nerveCNDcochlear nerve deficiencyFNfacial nerveFSEfast spin-echoIACinternal auditory canalIP-Iincomplete partition type IIP-IIincomplete partition type IISCCsemicircular canalSNHLsensorineural hearing lossVAvertebral artery